KONSTRUKSI TES KEBAHASAAN UAS SD di KAB. MADIUN - Nur Samsiyah; Apri Kartikasari H.S; Imam Gunawan; Chrisna Emilia (IKIP PGRI MADIUN, 2014)
Learning aims to achieve proficiency behasa properly. To achieve this goal of language learning can not be separated from the aspects of grammar. One way to achieve the grammar aspect is the test. Language tests can be called with the test language for principal goal is the ability to speak is not the knowledge of the language. Range measured aspects adhered to the types of tests used in the test item at the end of the lesson / test formatif.The reseach aims to determine aspects of language are tested at each end of the semester. This study used a qualitative approach to data sources such as the end of semester exam 1 and 2 grade 1 to grade 6. The reason for the selection of test questions daily as a subject of study as a matter of KKG was prepared by a team of Madiun Regency. techniques of data collection is done by collecting data sources in the field and read the data source. The data analysis phase consists of threesteps: data reduction, classification, presentation of data and drawing conclusions. The results showed there were aspects of language such as phonology (Fon/f.1, Fon/a/1, Fon/a.i, Fon/a.I, Fon/a.e-E, Fon/a.o-O) the aspect morphology consisting of a free morpheme and bound, the process of reduplication or repetition, syntactic aspects that form phrases and sentences and semantic aspects in the form of meaning.